Anisotropic ridge/groove microstructure for regulating morphology and biological function of Schwann cells. (March 2020) - Li, Guicai; Zhao, Xueying; Zhang, Luzhong; Yang, Jian; Cui, Wenguo; Yang, Yumin; Zhang, Hongbo
Abstract: Peripheral nerve regeneration is a clinical challenge that tremendously affected the patients' quality of life. Recently, anisotropic microtopology has shown promise in treating peripheral nerve regeneration. However, the systematically investigation of how micropatterning influence Schwann cells (SCs), including morphology, biofunction and gene expression etc, has never been investigated. Herein, we fabricated the chitosan micropatterning with four different ridge/groove (RG) and subsequently cultured the SCs on those samples. As a result, the SCs showed obvious orientationally growth to micropatterning and 30/30 μm size showed the best regulation effect. And in the meantime, 30/30 μm size did not affect the DNA synthesis phase of SC cells (G2 and S phase) and significantly down-regulated both the relative protein level of N- cadherin and β-catenin from SCs. More importantly, the anisotropic micropatterning could significantly up-regulate the expression of several key genes of SCs related to neuronal plasticity and axon regeneration (smad6), cytoskeleton development (β-actin) and myelination (MPZ). Overall, the results demonstrated that the anisotropic chitosan micropatterning with 30/30 μm size can regulate SCs' orientation well with a tendency to myelination; and the systemic evaluation provide mechanical understanding, which acts as important references for future design of anisotropic biomaterials for peripheral nerve regeneration.